134 Osgin1 and osgin2 regulate adhesion of HCAEC and potentially contribute to endothelial erosion overlying stenotic plaques. (June 2018) - White, Stephen; Satta, Sandro; Hazell, Georgina; Teasdale, Jack; Sala-Newby, Graciela; Johnson, Tom; Johnson, Jason; Newby, Andrew; Alexander, Yvonne
Abstract : Endothelial erosion of plaques is the underlying mechanism of approximately 30% of heart attacks. It describes a pathology where endothelial detachment from an intact fibrous cap (normally over a highly-stenotic plaque) precipitates thrombosis, triggering an acute coronary syndrome. We have developed an in vitro model to explore potential mechanisms involved in endothelial erosion, by mimicking the combined effects of endothelial dysfunction and elevated flow/shear (ESS) experienced over stenotic atherosclerotic plaques. Human coronary artery endothelial cells (HCAEC) exposed to 5 ng/ml TNF-α and aqueous cigarette smoke extract (CSE) suffered ~30% cell loss when adapted to elevated shear stress (ESS), with no cell loss observed under oscillatory shear stress. Treatment with apoptosis inhibitor (Z-VAD-FMK) or matrix metalloproteinase inhibitor (GM6001) did not prevent cell loss. A robust activation of Nrf2-regulated genes was observed by CSE, which was amplified under ESS by TNF-α. Inclusion of Nrf2 activators sulforaphane (2.5 µM) or isoliquiritigenin (10 µM) triggered ~80% cell loss at elevated shear stress with TNF-α and CSE, implying that hyperactivation of the Nrf2 system, may promote, rather than protect from cell detachment. Expression of both OSGIN1 and OSGIN2 were maximally increased under conditions where cells were detaching, and both were upregulated by Nrf2 activation. To investigate their role in detachment, they were overexpressed using adenoviral vectors. OSGIN1 +2 overexpression in static culture resulted in cell cycle arrest in S-phase (control –CTL v OSGIN1 +2: 5.5-fold, p=0.003), with a significant increase in the number of multinucleated cells (CTL v OSGIN1 +2: 4.5-fold, p=<0.001), with a concomitant reduction in G2/M (CTL v OSGIN1 +2: 4.9-fold reduction, p=0.084). Immunocytochemical analysis indicated loss of focal adhesions and stress fibres, dysregulation of autophagy and induction of senescence in HCAEC, with a significant increase in senescence-associated β-galactosidase staining (CTL v OSGIN1 +2: 6.7-fold, p=<0.001) and P16 expression (CTL v OSGIN1 +2: 3.2-fold, p=0.035). Importantly, OSGIN1 +2 overexpression induced cell detachment in the orbital shaker shear stress model (CTL v OSGIN1 +2: 6.8-fold, p≤0.001), which was independent of apoptosis. Taken together, sustained hyperactivation of Nrf2 may promote endothelial cell detachment, contributing to plaque erosion overlying stenotic plaques, potentially through the combined upregulation of OSGIN1 and OSGIN2.